Kontribusi Pendidikan Islam dalam Pengembangan Sosial Emosional Peserta Didik di MTs Salafiyah Syafiiyah Tebuireng Jombang - Hasan, Moch. Sya'roni; Aziz, Abdul (LP3M STIT Al Urwatul Wutsqo Jombang, 2023)
This study aims to explore and analyze the contribution of Islamic education to the social-emotional development of students at Madrasah Tsanawiyah (MTs) Salafiyah Syafiiyah Tebuireng, Jombang. This research uses a qualitative approach with a case study method. Data was collected through participatory observation, in-depth interviews with teachers and students, as well as analysis of documents related to the curriculum and Islamic education activities at MTs Salafiyah Syafiiyah Tebuireng. The results of this study indicate that Islamic education at MTs Salafiyah Syafiiyah Tebuireng has a significant contribution to the development of students' social-emotional aspects. Islamic education at MTs Salafiyah Syafiiyah Tebuireng instills Islamic moral and ethical values ??through religious learning and the practice of worship. This strengthens students' awareness of social responsibility, concern for others, and ability to manage and overcome emotions when interacting with others. The Islamic education curriculum, which is comprehensive and integrated with general education, provides a strong foundation for building students' social-emotional skills. In addition, MTs Salafiyah Syafiiyah Tebuireng also emphasizes character education by providing examples and guidance from teachers and staff who are Islamic role models. The supportive pesantren environment and the applied social norms also play an important role in shaping the social-emotional quality of students. The results of this study provide insight and a better understanding of the contribution of Islamic education to the socio-emotional development of students at MTs Salafiyah Syafiiyah Tebuireng. The implications of this research can be used as a reference for other Islamic educational institutions to strengthen the socio-emotional dimensions of students through an integrated approach between religious education, character education, and the educational environment